Efficiency comparison of apigenin-7-O-glucoside and trolox in antioxidative stress and anti-inflammatory properties. (2nd August 2020) - Wang, Wei; Yue, Ru-Feng; Jin, Zhen; He, Li-Min; Shen, Rong; Du, Dan; Tang, You-Zhi
Abstract: Objectives: Chamomile has long been used as a medicinal plant due to its antioxidative and anti-inflammatory activity. Apigenin-7-O-glucoside (AG) is one of the major ethanol extract components from chamomile; however, the underlying mechanism remains unclear. Methods: In this study, the antioxidant potential and the anti-inflammatory activities of AG were analysed and compared with those of trolox. We demonstrate the protective effects of AG on free radical-induced oxidative damage of DNA, proteins and erythrocytes. Flow cytometry assay was used to detect ROS production. Additionally, the expression of anti-oxidation-related and inflammation-related factors was detected by ELISA and Western blotting, respectively. Key findings: AG and trolox showed different efficiency as antioxidant in different experimental systems. AG had similar effect as trolox to inhibit H2 O2 -induced ROS production in RAW264.7 cells, while exerted stronger inhibition against free radical-induced oxidative damage on erythrocytes than trolox. Interestingly, compared with trolox, AG also had stronger inhibitory effect on LPS-induced NF-κB/NLRP3/caspase-1 signalling in RAW246.7 cells. Conclusions: These results suggest the potential of AG as a pharmaceutical drug for anti-oxidation and anti-inflammation, and the combined usage of AG and trolox might promote its efficacy. Our findings will provide new insights into the development of new drugs with antioxidative and anti-inflammatory functions.